Recurrent Diplopia in a Pediatric Patient with Bickerstaff Brainstem Encephalitis - Scott A. McLeod; Wallace Wee; Francois D. Jacob; Isabelle Chapados; Francois V. Bolduc (Case Reports in Neurological Medicine)
Introduction. Acute complete external ophthalmoplegia is a rare finding in clinical practice that is associated with diseases affecting the neuromuscular junction, the oculomotor nerves, or the brainstem. Ophthalmoplegia has been reported with acute ataxia in Miller Fisher syndrome (MFS) and Bickerstaff brainstem encephalitis (BBE). Up to 95% of these cases are associated with anti-GQ1b antibodies. Only a small number of cases of anti-GQ1b negative MFS have been documented in pediatric patients. This is the first case reporting a recurrence of ocular symptoms in an anti-GQ1b antibody negative patient with BBE. Case Presentation. An 8-year-old Caucasian boy presented with complete external ophthalmoplegia without ptosis, cerebellar ataxia, and a disturbance of consciousness. He had recently recovered from a confirmed Campylobacter jejuni infection. On subsequent laboratory testing he was anti-GQ1b antibody negative. He had a recurrence of diplopia at four-week follow-up. Conclusions. This patient’s recurrence of diplopia was treated with a five-week course of oral corticosteroids which did not worsen his condition, and this may be a therapeutic option for similar patients. We will discuss the symptoms and treatment of reported pediatric cases of anti-GQ1b antibody negative cases of MFS and the variation between cases representing a spectrum of illness.